2022
DOI: 10.3390/ijerph192315475
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Risk Factors of Melioidosis in Southeast Asia: A Scoping Review

Abstract: This scoping review aims to provide a comprehensive overview of human melioidosis in Southeast Asia as well as to highlight knowledge gaps in the prevalence and risk factors of this life-threatening disease using available evidence-based data for better diagnosis and treatment. Preferred Reporting Items for Systematic Review and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) was used as the guideline for this review. The literature search was conducted on 23 March 2022 through two electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…A more recent review paper estimated the overall prevalence of B. pseudomallei in Southeast Asia to be between 0.02% and 74.4% [ 9 ]. There is variation in the burden of disease between different geographic locations and patient groups; for example, in rural northeast Thailand, a study found an annual incidence of bacteraemic melioidosis to be 14–17 per 100,000 [ 10 ], whereas a study of children with suppurative parotitis in Cambodia found 74% had culture-confirmed B. pseudomallei [ 11 ].…”
Section: Melioidosismentioning
confidence: 99%
“…A more recent review paper estimated the overall prevalence of B. pseudomallei in Southeast Asia to be between 0.02% and 74.4% [ 9 ]. There is variation in the burden of disease between different geographic locations and patient groups; for example, in rural northeast Thailand, a study found an annual incidence of bacteraemic melioidosis to be 14–17 per 100,000 [ 10 ], whereas a study of children with suppurative parotitis in Cambodia found 74% had culture-confirmed B. pseudomallei [ 11 ].…”
Section: Melioidosismentioning
confidence: 99%
“…Unless looked with suspicion, these features can be easily misinterpreted as Pseudomonas or aerobic spore bearers. Automated tools like MALDI -TOF or VITEK 2 may not be definitive in Most cases presented in the critical stages of illness with multiple internal organ abscesses, pneumonia and sepsis [7]. The chronic disease occurs because of the organism's ability to survive inside macrophages, and can mimic granulomatous diseases [8].…”
Section: Radiological Investigationsmentioning
confidence: 99%
“…thailandensis and B. pseudomallei. B. pseudomallei , the causative agent of melioidosis, is an environmental pathogen known to inhabit both soil and water in sub-tropical and tropical regions, especially in Southeast Asia and Northern Australia [5–8]. The potential of B.…”
Section: Introductionmentioning
confidence: 99%
“…cepacia, B. mallei, B. thailandensis and B. pseudomallei. B. pseudomallei, the causative agent of melioidosis, is an environmental pathogen known to inhabit both soil and water in sub-tropical and tropical regions, especially in Southeast Asia and Northern Australia [5][6][7][8]. The potential of B. pseudomallei for use as a bioterrorism agent earns it its classification as a category B agent (second highest priority) by the Centers for Disease Control and Prevention (CDC) [9,10].…”
mentioning
confidence: 99%